Bioenergetic consequences of PINK1 mutations in Parkinson disease. - Andrey Yurevich Abramov; Matthew Gegg; Anne Grunewald; Nicholas William Wood; Christine Klein; Anthony Henry Vernon Schapira (PLoS ONE)
Background Mutations of the gene for PTEN-induced kinase 1 (PINK1) are a cause of familial Parkinson's disease (PD). PINK1 protein has been localised to mitochondria and PINK1 gene knockout models exhibit abnormal mitochondrial function. The purpose of this study was to determine whether cells derived from PD patients with a range of PINK1 mutations demonstrate similar defects of mitochondrial function, whether the nature and severity of the abnormalities vary between mutations and correlate with clinical features. Methodology We investigated mitochondrial bioenergetics in live fibroblasts from PINK1 mutation patients using single cell techniques. We found that fibroblasts from PINK1 mutation patients had significant defects of bioenergetics including reduced mitochondrial membrane potential, altered redox state, a respiratory deficiency that was determined by substrate availability, and enhanced sensitivity to calcium stimulation and associated mitochondrial permeability pore opening. There was an increase in the basal rate of free radical production in the mutant cells. The pattern and severity of abnormality varied between different mutations, and the less severe defects in these cells were associated with later age of onset of PD. Conclusions The results provide insight into the molecular pathology of PINK1 mutations in PD and also confirm the critical role of substrate availability in determining the biochemical phenotype--thereby offering the potential for novel therapeutic strategies to circumvent these abnormalities.